Chartergellus golfitensis West-Eberhard: a new species of Neotropical swarm-founding wasp (Hymenoptera: Vespidae, Polistinae) with notes on the taxonomy of Chartergellus zonatus Spinola - Jane West-Eberhard, Mary (2010)
Chartergellus golfitensis West-Eberhard new species, is described from Central America and compared with C. zonatus Spinola, a species heretofore inadequately described.